The Concepts Of "Mythology", "Linguaculturology", "Intercultural Relations" In Modern English Linguistics - Pulatova Sarvinoz Botir kizi (Genius Journals, 2021)
This article is devoted to the views of several scholars on the specifics of the concepts of "mythology", "linguaculturology", "intercultural relations". It has also been suggested that a number of factors contribute to the interdependence of these lexeme units. In recent years, linguists to the problems of the language and culture of a particular ethnic group have paid much attention. The article pays attention to such concepts as a conceptual and linguistic worldview and their relationship.
Keywords: Mythologeme; mythology; linguaculturology; lexical units with a mythological component of meanin